2006
DOI: 10.1056/nejmoa055120
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide versus Placebo in Scleroderma Lung Disease

Abstract: One year of oral cyclophosphamide in patients with symptomatic scleroderma-related interstitial lung disease had a significant but modest beneficial effect on lung function, dyspnea, thickening of the skin, and the health-related quality of life. The effects on lung function were maintained through the 24 months of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
1,063
6
70

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,492 publications
(1,214 citation statements)
references
References 22 publications
36
1,063
6
70
Order By: Relevance
“…However, although the effects were statistically significant, they were mild to moderate and of questionable clinical significance (15). Similar findings were also observed with intravenous pulse cyclophosphamide (15). This is the first report of improvement in functional and morphologic parameters in a patient with pulmonary fibrosis upon treatment with imatinib mesylate.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…However, although the effects were statistically significant, they were mild to moderate and of questionable clinical significance (15). Similar findings were also observed with intravenous pulse cyclophosphamide (15). This is the first report of improvement in functional and morphologic parameters in a patient with pulmonary fibrosis upon treatment with imatinib mesylate.…”
Section: Discussionsupporting
confidence: 56%
“…In the scleroderma lung study, treatment with oral cyclophosphamide at a dosage of Յ2 mg/kg/day for 12 months resulted in statistically significant improvement. However, although the effects were statistically significant, they were mild to moderate and of questionable clinical significance (15). Similar findings were also observed with intravenous pulse cyclophosphamide (15).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In contrast to idiopathic pulmonary fibrosis (IPF), which is an aggressive and rapidly progressive disease, SSc-ILD progresses more slowly (2). A recent placebo-controlled, double-blind study showed a statistically significant but modest (2.53%) beneficial effect of oral cyclophosphamide on lung function, as measured by forced vital capacity (FVC) (3). This small effect was not persistent at 1 year of followup (4), although the patients who had received cyclophosphamide still demonstrated a benefit in the dyspnea score.…”
mentioning
confidence: 99%
“…Patients with abnormal findings on bronchoalveolar lavage (BAL) have evidence of active interstitial lung disease and may experience a decline in lung function and in radiographic progression of ILD as compared with those with normal BAL findings (4)(5)(6)(7)(8). Analysis of BAL fluid can serve as an intermediate measure of disease activity; however, its role in predicting lung function and in guiding treatment decisions in scleroderma patients is unknown.…”
Section: Conclusion Persistently Abnormal Results On Bal Fluid Analymentioning
confidence: 99%